Implementation of Field Experience Practice Activities in Shaping the Professionalism of Prospective Teachers at Muhammadiyah 14 Siabu Vocational School - Uswatun Hasanah; Laila Saqila Putri; Syarifah Syarifah; Yusfi Latifah; Nur Aisyah; Nurhalimah Siregar; Nur Aminah; Siti Aminah; Kasman Kasman (AMK : Abdi Masyarakat UIKA, 2026)
This study aims to analyze the implementation of Field Experience Practice (PPL) activities in developing the professionalism of prospective teachers at SMK Muhammadiyah 14 Siabu. This study used a qualitative approach with a descriptive-reflective design. The subjects were eight students from the English Language Education, Science Education, Islamic Religious Education, and Islamic Education Management study programs who participated in the PPL and acted as reflective researchers. Data were obtained through participant observation, learning tool documentation, reflective journals, and group discussions. Then, they were analyzed qualitatively based on indicators of pedagogical, professional, social, and personality competencies. The results indicate that the implementation of PPL significantly contributed to improving students' abilities to systematically design, implement, and evaluate learning. Furthermore, the PPL activities strengthened mastery of teaching materials, developed communication and collaboration skills, and fostered a sense of responsibility, discipline, and professional ethics as prospective educators. The ongoing reflection process also deepened students' understanding of the meaning of teacher professionalism. Thus, PPL can be viewed as a strategic tool in preparing prospective teachers who are competent, professional, and possess integrity.